Genome-wide association study of soybean (Glycine max [L.] Merr.) germplasm for dissecting the quantitative trait nucleotides and candidate genes underlying yield-related traits - Rani, Reena; Raza, Ghulam; Ashfaq, Hamza; Rizwan, Muhammad; Razzaq, Muhammad Khuram; Waheed, Muhammad Qandeel; Shimelis, Hussein; Babar, Allah Ditta; Arif, Muhammad (Frontiers in Plant Science, 2023)
Soybean (Glycine max [L.] Merr.) is one of the most significant crops in the world in terms of oil and protein. Due to rising demands of soybean products the need for improved varieties has increased for productive farming. However, complex correlation patterns among quantitative traits along with genetic interactions pose a challenge for soybean breeding. Association studies play an important role in the identification of accession with useful alleles by locating genomic sites associated with the phenotype in germplasm collections. In the present study, a genome-wide association study was carried out for seven agronomic and yield-related traits. A field experiment was conducted in 2015/2016 at two locations that include 155 diverse soybean germplasm. These germplasms were genotyped using SoySNP50K Illumina Infinium Bead-Chip. A total of 51 markers were identified for node number, plant height, pods per plant, seeds per plant, seed weight per plant, hundred-grain weight and total yield using a multi-locus linear mixed model (MLMM) in FarmCPU. Among these significant SNPs, 18 SNPs were putative novel QTNs while 33 SNPs co-localized with previously reported QTLs. A total of 2356 genes were found in 250kb upstream and downstream of significant SNPs of which 17 genes were functional while the remaining were hypothetical proteins. These 17 Candidate genes were located in the region of 14 QTNs of which ss715580365, ss715608427, ss715632502 and ss715620131 are novel QTNs for PH, PPP, SDPP and TY respectively. Four candidate gene Glyma.01g199200, Glyma.10g065700, Glyma.18g297900 and Glyma.14g009900 were identified in the vicinity of these novel QTNs that encode lsd one like 1, Ergosterol biosynthesis ERG4/ERG24 family, HEAT repeat-containing protein and RbcX2 respectively. Although further experimental validation of these candidate genes is required, several of these genes appear to be involved in growth and developmental processes related to the respective agronomic traits by comparing them with their homologs in Arabidopsis thaliana. This study supports the usefulness of association study and provides valuable data for functional markers and investigating candidate genes within a diverse germplasm collection in future breeding programs.